Nilai-Nilai Pendidikan Islam Dalam Qur’an Surat Luqman Ayat 13-19 (Kajian Ilmu Pendidikan Islam) - Izzan, Ahmad; Rajabi, Fahmi (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
Education in Islam is inseparable from its primary sources of teaching, namely the Qur’an (including hadith and ijtihad). The Qur’an, as a guide and reference, provides broad guidelines and general principles regarding education from its perspective. The Qur’an contains numerous aspects of human life, offering unmatched guidance and wisdom about life, nature, and its contents, which remain inexhaustible for study and reflection. Surah Luqman, verses 13–19, presents several educational values encompassing the values of faith (aqidah), law (sharia), and morality (akhlaq). This study aims to describe the Islamic educational values contained in Surah Luqman, verses 13–19, within the scope of Islamic Education Studies. This research is a library study, which involves examining the interpretations of exegetes (mufassirun) regarding Surah Luqman, verses 13–19, along with written sources on Islamic educational values provided by scholars. The research method employed is a qualitative approach, focusing on content analysis of the Qur’an (Surah Luqman 13–19) and relevant literature. Based on the findings, it can be concluded that the values contained in these verses include aqidah values, such as the prohibition of associating partners with Allah, the certainty of consequences for every deed, and the reality of the final return. The sharia values identified include the prohibition of obeying parents when their commands deviate from Islamic teachings, the establishment of prayer, doing good, and enjoining what is right while forbidding what is wrong. Finally, the akhlaq values emphasized include gratitude, humility (avoiding arrogance), and simplicity in life.  Keywords: Islamic educational values, Islamic education studies